Expression of Insulin-like growth factor 2 mRNA-binding protein 3 and its diagnostic value in breast cancer - Wang, Chao-Qun; Shao, Jun-Kang; Wang, Yan; Lu, Shi-Ping; Jiang, Li-Jing; Du, Zhi-Qun; Huang, Bi-Fei (Frontiers in Oncology, 2025)
There is currently no established systematic explanation of the clinical application and diagnostic value of insulin-like growth factor 2 mRNA-binding protein 3 (IGF2BP3) in breast cancer. This study utilized immunohistochemistry (IHC) to assess the expression of the IGF2BP3 protein in 299 cases of breast cancer tissues, with the aim of investigating the clinical and diagnostic significance of IGF2BP3 in breast cancer. Our results showed that the positivity rate of IGF2BP3 in breast cancer tissues was 11.4% (34/299), significantly higher than that in normal breast tissues (0.0%, 0/60) (P=0.006). IGF2BP3 levels were found to be elevated in breast cancer cases with higher tumor grade, ER negative, PR negative, HER2 negative, higher Ki-67 index, and the triple-negative breast cancer (TNBC) molecular subtype (all P<0.05). Conversely, the presence of IGF2BP3 was less common in breast cancer cases with axillary lymph node metastasis and advanced tumor stage (both P<0.05). In a multiple logistic regression analysis, the independent predictors of IGF2BP3 expression in breast cancer were TNBC status (odds ratio = 3.408; 95% confidence interval: 1.026–11.321; P=0.045) and axillary lymph node metastasis (0.200; 0.068–0.593; P=0.004). We further analyzed the value of IGF2BP3 in the differential diagnosis of breast cancer and normal breast tissue, as well as the differential diagnosis of TNBC and non-TNBC. The results showed that the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of IGF2BP3 positive prediction for breast cancer were 11.4%, 100.0%, 100.0%, and 18.5%, respectively; and for TNBC, the corresponding values for IGF2BP3 positive prediction were 38.0%, 98.2%, 88.2%, and 81.5%, respectively. In all breast cancer or TNBC patients, no clear relationship between patient prognosis and IGF2BP3 expression was observed. We suggest that IGF2BP3 is upregulated in breast cancer, especially in TNBC, and has potential diagnostic value for breast cancer and TNBC.